TIMSS vs. PISA: what can they tell us about student success?—a comparison of Swedish and Norwegian TIMSS and PISA 2015 results with a focus on school factors - Laukaityte, Inga; Rolfsman, Ewa; Wiberg, Marie (Frontiers in Education, 2024)
This paper explores the measurement capabilities of the Trends in International Mathematics and Science Study (TIMSS) and the Programme for International Student Assessment (PISA) in assessing school factors that influence student performance. We specifically focus on the 2015 assessments of the science performance of 8th graders in Sweden and Norway. This was the latest year when the two assessments were conducted in the same year and science was the major subject area in the PISA assessment, which was essential for maximizing the assessments' comparability. Using multilevel models, the study identifies common and unique factors across the assessments and investigates the factors that influence student performance at different proficiency levels. The findings highlight the importance of school-level factors, which are significant in both assessments. Moreover, both assessments provide information on overlapping sets of factors that have varying influence on the performance of students with different proficiency levels. Overall, there are limited common factors between TIMSS and PISA. School factors vary between low-performing and highperforming schools, with differing significance in Norway and Sweden. The results indicate that TIMSS and PISA assessments offer complementary information, particularly for low-performing schools. Our findings suggest that different school types may benefit or suffer from distinct school factors. The findings are relevant for both educational professionals and policy-makers. Over the years, numerous studies have investigated various aspects of TIMSS and PISA data. However, most have focused solely on either TIMSS or PISA (see e.g., Teig, Sherer & Vegar Olsen, 2022), including several that have addressed Nordic results (e.g.